2021
DOI: 10.1186/s12913-021-06802-9
|View full text |Cite
|
Sign up to set email alerts
|

Incremental burden of comorbid major depressive disorder in patients with type 2 diabetes or cardiovascular disease: a retrospective claims analysis

Abstract: Background The estimated prevalence of comorbid major depressive disorder (. MDD) is 11% in patients with type 2 diabetes (T2D) and 15–20% in those with cardiovascular disease (CVD). Comorbid MDD continues to be a significant source of economic burden to the healthcare system. Methods We assessed the incremental healthcare burden of comorbid MDD in patients with T2D or CVD. This real-world, retrospective, administrative claims study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Some researchers have also pointed out that the HPA axis function is very hyperactive in patients with depression, which promotes the production and release of a large number of adrenal cortex hormones. The confusion occurs with thickening the blood and greatly increasing the risk of coronary heart disease [14] . Conventional…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have also pointed out that the HPA axis function is very hyperactive in patients with depression, which promotes the production and release of a large number of adrenal cortex hormones. The confusion occurs with thickening the blood and greatly increasing the risk of coronary heart disease [14] . Conventional…”
Section: Resultsmentioning
confidence: 99%
“…A recent retrospective investigation focusing on the increasing trend of comorbid MDD in patients with T2DM or CVD reflected that extensive use of healthcare facilities and higher expenditure was involved in the patients with either T2DM or CVD and comorbid MDD compared to the patients without MDD. Another recent scientific investigation revealed that one in every five individuals with T2DM had mental health issues associated with increased healthcare utilization [ 11 , 12 ]. According to the Adult Treatment Panel III of the National Cholesterol Education Program (NCEP), at least three of the five risk factors-abdominal obesity, high triglycerides, low HDL-must be present (HDL), hypertension and a rise in glucose levels had been associated with metabolic syndrome (MS) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%